ANALISIS IMPLEMENTASI KONSEP SUBROGASI DALAM PENJAMINAN KREDIT SYARIAH BERDASARKAN POJK NOMOR 11 TAHUN 2025: STUDI KASUS PADA PT PENJAMINAN KREDIT DAERAH BANTEN (JAMKRIDA BANTEN): An Analysis of the Implementation of the Subrogation Concept in Sharia-Compliant Credit Guarantee Schemes under POJK Regulation Number 11 of 2025: A Case Study of PT Penjaminan Kredit Daerah Banten (Jamkrida Banten) - Abdul Hamid Arribathi; Bangkit Mulia Ramadhan (Jurnal Investasi, 2026)
This study aims to analyze the application of the subrogation concept in sharia credit guarantee activities at PT Penjaminan Kredit Daerah Banten (Jamkrida Banten) based on the Financial Services Authority Regulation (POJK) Number 11 of 2025 concerning the Implementation of Guarantee Institution Business. Subrogation is the right of the guarantee institution to take over the right to collect from the creditor against the debtor after the guarantee institution makes a claim payment. In the context of a sharia guarantee institution, the concept of subrogation needs to be adjusted to the principles of justice and compliance with Islamic law (fiqh muamalah). This study uses a descriptive qualitative approach with a content analysis method of Jamkrida Banten's internal policy documents, OJK regulations, and civil law and sharia economic law literature. The results of the study indicate that the application of subrogation at Jamkrida Banten is still in the policy adjustment stage, especially in the preparation of the mechanism for transferring post-claim collection rights and the governance of subrogated assets. This study recommends strengthening internal regulations, training human resources, and digitizing the subrogation management process to ensure compliance with Sharia principles and OJK regulations.